1990 grain dust explosions stay low - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Fifteen grain dust explosions were reported in the U.S. in 1990 according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This compares LO 13 in 1989 and a len-year average of 20 explosions.
Keywords: Grain dust; Dust explosions